Monsters don't scuba dive - Dadey, Debbie; Jones, Marcia (Marcia Thornton); Gurney, John Steven, 1962- (New York : Scholastic, 1995)
Could the swimming teacher at Camp Lone Wolf really be a sea monster? The Bailey School Kids are going to find out!
"A Little Apple paperback."
620
Keywords: Bailey School kids (Fictitious characters) -- Fiction